Women and the Press The Struggle for Equality - Bradley, Patricia (Northwestern University Press, 2005)
When Abigail Adams made her famous plea to John Adams to "remember the ladies," the role of advocacy on behalf of U.S. gender equality began its rocky and still uncompleted journey. In Women and the Press, Patricia Bradley examines the tensions that have arisen over the course of this journey as they relate to women in journalism. From their first entrance into the commercial press as sentimental writers, to the present day, the call for gender equality has had special meaning for female journalists. Is there a role, a responsibility, for advocacy, even subversion, in a newsroom setting? This is an account of how women in journalism sought to integrate the need for gender equality with the realities of the journalistic workplace.